Effect of ligand type on CO2 adsorption over amine functionalized fibrous adsorbents - Mohamad, N.A. (Institute of Physics Publishing, 2020)
In this study, ligands originated from glycidyl methacrylate (GMA) and vinyl benzyl chloride (VBC) monomers were grafted onto fibrous polyethylene/polypropylene (PE/PP) substrate and the resulting grafted copolymers were functionalized with ethylenediamine (EDA). The changes in the chemical structure and crystallinity of the aminated adsorbents were evaluated using Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD), respectively. The PE/PP-g-PGMA-EDA adsorbent showed a CO2 adsorption capacity of 1.73 mmol/g from pure gas, which is 87 lower than that of PE/PP-g-PVBC-EDA (3.24 mmol/g) at 30 bars despite the higher density in the former adsorbent. The effect of temperature, selectivity and CO2 gas composition was further investigated for the PE/PP-g-PVBC-EDA adsorbent. Â© Published under licence by IOP Publishing Ltd.